Evaluation of Citizenship Education Learning Process Assessment - Delfiyan Widiyanto; Annisa Istiqomah (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The purpose of this research is to know the evaluation of assessment of learning process of Citizenship education . Assessment of learning process as uaoaya to improve the quality of learning. The assessment of the learning process is conducted to measure the efficient, effective, and productivity of learning activities. Implementation of the 2013 curriculum has obstacles in starting from planning, implementation, and reporting. Implementation of curriculum implementation there are constraints on the use of learning methods, lack of time in learning activities, lack of learning materials, attitude difficulties, and curriculum facilities 2013 at SMA N se Palembang. Preliminary observation on the aspect of the assessment of the learning process conducted in SMA N in Gunungkidul District that less attention for assessment of the learning process. Type of research conducted with the type of evaluation of discrepancy model with quantitative descriptive approach . The research was conducted in SMA N of Gunungkidul Regency consisting of 11 senior high schools with 16 respondents of Citizenship education teachers using the 2013 curriculum. The results showed that the assessment of the learning process was carried out very well. Assessment process assessment consists of components namely planning, implementation, and results lapoaran. The planning stage is an excellent category with a t-score of 54.6186 , the implementation stage of the assessment of the learning process including the category is very good with t-score of 49.65875 , and the reporting stage of the results of the assessment process included the category less with a t-score of 20.93 . In the comparison stage of learning process gap disparity shows the percentage of the assessment plan implemented 98 % , the percentage of the implementation of the assessment is done 91% , and the percentage of assessment report of the learning process is done 45%.